Academic Senate Minutes 2004-04-01 - Academic Senate:::::::::
Chair Report. Agenda - Approved. Minutes of 3/10/22 - Approved. President Report. Provost Report. Changes to Wellness Check-in. From EPC: Revisions to Electrical Engineering BS - approved for Senate Consent Calendar. Vice President of Administration and Finance. Student Representative Report. From EPC: Revision to the BA in Business Administration - approved for Senate Consent Calendar. From APARC: Priority Recommendations - approved for Senate Agenda. From SAC: Revision to the Attendance Policy - approved for Senate Agenda. Learning Objectives for Orientation approved as Information Item. Vice President of Student Affairs Report. Senate Agenda approved. Good of the Order. CFA Report.